1994
DOI: 10.1364/josaa.11.001929
|View full text |Cite
|
Sign up to set email alerts
|

Image enhancement for the visually impaired: the effects of enhancement on face recognition

Abstract: Image enhancement has been shown to improve face recognition by visually impaired observers. We conducted three experiments in an effort to refine our understanding of the parameters leading to this effect. In experiment 1 we found that the band of spatial frequencies between 4 and 8 cycles/face is critical for face recognition. In experiment 2 we found that enhancement of these frequencies and the resulting image distortion actually reduced recognition performance for normal observers. Since the degradation o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

5
94
1

Year Published

2005
2005
2022
2022

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 105 publications
(100 citation statements)
references
References 10 publications
5
94
1
Order By: Relevance
“…In particular, Peli et al studied the visually impaired individuals' recognition of faces [2]. Everingham et al [3] used a technique to identify objects in images and colour these using saturated colours.…”
Section: Related Workmentioning
confidence: 99%
See 1 more Smart Citation
“…In particular, Peli et al studied the visually impaired individuals' recognition of faces [2]. Everingham et al [3] used a technique to identify objects in images and colour these using saturated colours.…”
Section: Related Workmentioning
confidence: 99%
“…Challenges with social interaction and recognizing faces were also identified by Cimarolli et al [16] and the mechanisms of recognizing faces has been addressed in the early work by Peli et al [2]. Beyond that, the research into face recognition aids is limited.…”
Section: Recognizing Facesmentioning
confidence: 99%
“…The presence of non-geometric features could hinder learning if they are hard to identify or are treated as visual clutter rather than useful information. The idea of contrast enhancement for low vision is incorporated into closed-circuit TV (CCTV) magnifiers (Lund & Watson, 1997) and has been explored in image-enhancement algorithms for face recognition (Peli, Lee, Trempe, & Buzney, 1994) and TV images (Peli, 2005).A practical goal of this experiment was to assess the potential utility of virtual visual displays as navigation aids for low vision. Blind individuals can use tactile maps (Holmes, et al, 1996) and verbal descriptions of layout geometry (Giudice, 2004;Giudice, Bakdash, & Legge, 2007) to learn a layout before visiting it.…”
mentioning
confidence: 99%
“…Image resolution has been shown to be very important in other kinds of displays, such as those featuring shape from shading. Studies using blocking or low-pass filtering have shown that face identification using shape from shading can be disrupted or may even be impossible when the resolution is below a certain limit (Costen, Parker, & Craw, 1994, 1996Harmon, 1973;Peli, Lee, Trempe, & Buzney, 1994).…”
mentioning
confidence: 99%